Tick-borne encephalitis virus (TBEV) prevalence in field-collected ticks (Ixodes ricinus) and phylogenetic, structural and virulence analysis in a TBE high-risk endemic area in southwestern Germany - Ott, Daniela; Ulrich, Kristina; Ginsbach, Philip; Öhme, Rainer; Bock-Hensley, Oswinde; Falk, Ulrich; Teinert, Martina; Lenhard, Thorsten (Parasites & vectors, 2020)
Tick-borne encephalitis (TBE) is the most common viral CNS infection with incidences much higher than all other virus infections together in many risk areas of central and eastern Europe. The Odenwald Hill region (OWH) in southwestern Germany is classified as a TBE risk region and frequent case numbers but also more severe infections have been reported within the past decade. The objective of the present study was to survey the prevalence of tick-borne encephalitis virus (TBEV) in Ixodes ricinus and to associate TBEV genetic findings with TBE infections in the OWH. Ticks were collected by the flagging methods supported by a crowdsourcing project implementing the interested public as collectors to cover completely and collect randomly a 3532 km2 area of the OWH TBE risk region. Prevalence of TBEV in I. ricinus was analysed by reversed transcription quantitative real-time PCR. Phylogeographic analysis was performed to classify OWH TBEV isolates within a European network of known TBEV strains. Mutational sequence analysis including 3D modelling of envelope protein pE was performed and based on a clinical database, a spatial association of TBE case frequency and severity was undertaken. Using the crowd sourcing approach we could analyse a total of 17,893 ticks. The prevalence of TBEV in I. ricinus in the OWH varied, depending on analysed districts from 0.12% to 0% (mean 0.04%). Calculated minimum infection rate (MIR) was one decimal power higher. All TBEV isolates belonged to the European subtype. Sequence analysis revealed a discontinuous segregation pattern of OWH isolates with two putative different lineages and a spatial association of two isolates with increased TBE case numbers as well as exceptional severe to fatal infection courses. TBEV prevalence within the OWH risk regions is comparatively low which is probably due to our methodological approach and may more likely reflect prevalence of natural TBEV foci. As for other European regions, TBEV genetics show a discontinuous phylogeny indicating among others an association with bird migration. Mutations within the pE gene are associated with more frequent, severe and fatal TBE infections in the OWH risk region.